Pedagogical conceptions and method of teaching: the textbook Processologia na Escola Primária - Valdemarin, Vera Teresa; Campos, Daniela Gonçalves dos Santos (Paidéia (Ribeirão Preto), 2007)
The article focuses on the analysis of the textbook Processologia in Primary School, by Caio de Figueiredo Silva, published in 1956. The goal is to understand the process of incorporating pedagogical conceptions from the Progressive School in prescriptions to the pedagogical practice. The method used was the analysis of speech expressed in primary sources allied to historical references. The textbook allows to elucidate aspects of innovating pedagogical ideas and maintenance processes in education. It seems to be possible to show the influence of established tradition and the importance of textbooks used as instruments for the diffusion and circulation of ideas.